Potassium release potential of rubber growing soils in North-East India - Mandal D; Baruah T C (Rubber Science, 2016)
Studies on potassium (K) release potential of rubber growing soils in three states of North-East (NE) India namely Assam, Meghalaya and Tripura was carried out. Results revealed that rubber growing soils of Meghalaya could supply K to plant at a higher rate than the other two States of NE India as indicated by its higher K releasing parameters viz constant rate K (1.38 mg 100 g-1), step K (101.8 mg 100g -1) and cumulative K release potential (113.4 mg 100 g-1). Rubber growing soils of Tripura with high content of low active kaolinite clay recorded lower values of various K releasing parameters vis-a-vis low plant available K. Significant positive relationship of silt+ clay with K release parameters suggested that finer fractions of soil played an important role in K release. Step K and constant rate K showed positive and significant relationship with exchangeable and non-exchangeable K, whereas, cumulative K showed significant relationship with non-exchangeable pool of K only. Data indicated that K releasing power of soils is the sum of exchangeable and non-exchangeable form of soil K and long term availability of soil K to plants depends mainly upon its on-exchangeable pool. Total K ranged from 0.67 to 1.51 per cent and did not record significant relationship with K releasing parameters indicating that the major share of mineral K is not available for plant uptake. Results also suggested that K supplying power under rubber growing soils of Meghalaya may exhaust quickly due to its higher K releasing parameters which necessitates constant monitoring of K fertility status of these soils.
Keywords: Potassium availability; Potassium-release potential; Rubber growing soils; Soil properties